Effect of Different Levels of Energy and Protein in Total Mixed Ration on Body Weight, Body Condition Score and Body Measurement in Crossbred Heifer-Calves - Trivedi, Pankaj G; Lunagariya, Pravin M; Vaidh, Palak P; Parmar, Chirag P; Sorathiya, Kamlesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The experiment was aimed to evaluate the impact of varying energy and protein levels in a total mixed ration on body weight, body  weight gain, body condition score (BCS), and body measurement in crossbred heifer-calves. A total of 24 crossbred heifer-calves (75%  Holstein Friesian x 25% Kankrej) 4-6 months old, with similar growth and body weight were randomly allocated to four treatment  groups, each consisting of six calves. The calves in groups T1, T2, T3, and T4 were fed TMR having 12.60% crude protein (CP) & 2.028 Mcal  metabolizable energy (ME)/kg feed, 14.30% CP & 2.131 Mcal ME/kg feed, 15.98% CP & 2.244 Mcal ME/kg feed, and 17.58% CP & 2.307  Mcal ME/kg feed, respectively, for 140 days. The mean body weight was not significantly (p>0.05) affected among treatment groups,  while total body weight gain (kg) and heart girth gain (cm) were significantly (p
Keywords: Body condition score, Body measurement, Body weight, Crossbred heifer calves, Energy and protein level, Total mixed ration